2013
DOI: 10.1128/cvi.00280-12
|View full text |Cite
|
Sign up to set email alerts
|

An Adenovirus-Vectored Nasal Vaccine Confers Rapid and Sustained Protection against Anthrax in a Single-Dose Regimen

Abstract: cBacillus anthracis is the causative agent of anthrax, and its spores have been developed into lethal bioweapons. To mitigate an onslaught from airborne anthrax spores that are maliciously disseminated, it is of paramount importance to develop a rapidresponse anthrax vaccine that can be mass administered by nonmedical personnel during a crisis. We report here that intranasal instillation of a nonreplicating adenovirus vector encoding B. anthracis protective antigen could confer rapid and sustained protection a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
15
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 44 publications
(51 reference statements)
1
15
0
1
Order By: Relevance
“…Intranasal vaccination with AdVAV was well tolerated in this study, consistent with previous data obtained in mice (10). Replication-deficient adenoviral vectors have been extensively studied as vehicles for gene therapy and vaccine delivery.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Intranasal vaccination with AdVAV was well tolerated in this study, consistent with previous data obtained in mice (10). Replication-deficient adenoviral vectors have been extensively studied as vehicles for gene therapy and vaccine delivery.…”
Section: Discussionsupporting
confidence: 90%
“…The duration of the immune response is a hallmark of AdVAV vaccine activity. When a single intranasal dose of AdVAV was used to vaccinate A/J mice, anti-PA IgG ELISA titers in the vaccinated mice were maintained at the 1-month postvaccination level for at least 1 year (10).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, a number of studies indicated that administration of Ad5-vectored vaccines via the i.n. route might overcome preexisting immunity against the Ad5 vector (72)(73)(74)(75). We did observe slightly lower Y. pestis antigen-specific antibody titers in mice with the preexisting adenoviral immunity than in those animals without the preexisting adenoviral immunity when mice were i.n.…”
Section: Discussionmentioning
confidence: 55%
“…After that, the Ad vector expressing the B. anthracis PA domain 4 was developed for security reasons (32), and the primeboost vaccination strategy was also studied (33). Recently, Zhang et al (34) proved that an adenovirus-vectored nasal vaccine conferred rapid and sustained protection against anthrax in a singledose regimen. However, intramuscular inoculation with Ad5-PAopt in our work induced a faster immune response than intranasal route did in Zhang's work, even in the presence of PEI.…”
Section: Discussionmentioning
confidence: 99%